β-Amyloid 25-35 Peptide Reduces the Expression of Glutamine Transporter SAT1 in Cultured Cortical Neurons - Buntup, Doungjai (Springer US, 2007)
β-Amyloid (Aβ) peptides may cause malfunction and death of neurons in Alzheimer’s disease. We investigated the effect of Aβ on key transporters of amino acid neurotransmission in cells cultured from rat cerebral cortex. The cultures were treated with Aβ(25-35) at 3 and 10 μM for 12 and 24 h followed by quantitative analysis of immunofluorescence intensity. In mixed neuronal–glial cell cultures (from P1 rats), Aβ reduced the concentration of system A glutamine transporter 1 (SAT1), by up to 50% expressed relative to the neuronal marker microtubule-associated protein 2 (MAP2) in the same cell. No significant effects were detected on vesicular glutamate transporters VGLUT1 or VGLUT2 in neurons, or on glial system N glutamine transporter 1 (SN1). In neuronal cell cultures (from E18 rats), Aβ(25-35) did not reduce SAT1 immunoreactivity, suggesting that the observed effect depends on the presence of astroglia. The results indicate that Aβ may impair neuronal function and transmitter synthesis, and perhaps reduce excitotoxicity, through a reduction in neuronal glutamine uptake.